Volume 6: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27228
|View full text |Cite
|
Sign up to set email alerts
|

CFD Study of HPT Blade Cooling Flow Supply Systems

Abstract: This work summarizes the results of the CFD analyses to investigate the effect of the geometrical parameters for a typical coverplate-disk cavity and blade broach system also known as the blade cooling flow supply system. A turbofan high pressure turbine was used as the test vehicle for this investigation. The main objective was to explore potential improvements in engine SFC (aerodynamic performance) by reducing the parasitic work while minimizing the impact on the factors that affect the durability of the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The results showed that two pre-swirl systems have very similar characteristics. ElSadi et al [24] also compared the performance of the radial and axial pre-swirl system, and they found that compared with the radial pre-swirl system, the axial pre-swirl system had a positive impact on the parasitic work and blade feed temperature while it had a negative impact on the blade feed pressure.…”
Section: Introductionmentioning
confidence: 96%
“…The results showed that two pre-swirl systems have very similar characteristics. ElSadi et al [24] also compared the performance of the radial and axial pre-swirl system, and they found that compared with the radial pre-swirl system, the axial pre-swirl system had a positive impact on the parasitic work and blade feed temperature while it had a negative impact on the blade feed pressure.…”
Section: Introductionmentioning
confidence: 96%
“…Regarding the geometrical parameters in a cover-plate pre-swirl system, Ei-Sadi et al [17] investigated the effects of the cavity shapes and the position of pre-swirl nozzle on the parasitic work. Unlike the traditional pre-swirl system, Jarzombek et al [18] dealt with a high-radius pre-swirl system where the pre-swirl nozzles were located at a larger radius than the receiver holes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are sensors on this engine to monitor thrust, RPM, and fuel flow rate. Also, Elsadi et al [5] studied a turbofan high pressure turbine was used as the test vehicle for this investigation. The main objective was to explore potential improvements in engine SFC (aerodynamic performance) by reducing the parasitic work while minimizing the impact on the factors that affect the durability of the turbine blades, feed pressure, temperature, and mass flow.…”
Section: Introductionmentioning
confidence: 99%